Issues of working women in work-life ballance - Ismail, Nur Syakiran Akmal; Hassan, Kalthum (2020)
Many studies have discovered that young working mothers have difficulties in balancing between work and family life. Lacked of social and physical support on childcare and house work management has some influence on their job performance. It may result in less productivity, inefficient and ineffective job management. Therefore, the fundamental issues and problems faced by married working women in managing work life balance are the additional support system, infrastructure and services. This paper reviews the contributing factors to issues and problems faced by working women in the context of work-life balance. The method of this study is quantitative. This study involves respondents working as administrative and supporting staff in various government agencies in Tun Abdul Razak Complex (KOMTAR), Penang. The findings of the study would be able to help related agencies to provide the appropriate services, infrastructure and support systems to ease the burden of women in managing their families and hence to improve their work-life balance.